PENGARUH KARAKTERISTIK INDIVIDU DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT BATAM TEKNOLOGI GAS - LIM, STEPHEN; Rustam, Triana Ananda (LPPM Universitas Putera Batam, 2021)
In an organization, a main guideline for the company in achieving the goals set is a response from human resources. This statement requires a workforce capable of managing company activities. In this study, to determine and analyze the effect of individual characteristics and work environment on employee performance at PT Batam Teknologi Gas. PT Batam Teknologi Gas has employees with inaccurate characteristics in recording stock, so they often experience the stocks don’t match, lack of work among employees, which results in many delayed tasks, and less initiative to jointly build a better company. In terms of the inadequate work environment, such as lack of air ventilation in the room, lack of lighting in the room, and disturbing noise when carrying out the assigned tasks. Population of PT Batam Teknologi Gas has 212 employees. Simple random sampling technique is a random sampling technique without paying attention to special criteria, in calculating the number of samples using the Slovin formula with a sample of 139 employees. Data collection techniques in this study using a questionnaire and method uses SPSS 25. Based on the test results, the individual characteristics and the work environment simultaneously have a positive and significant influence on employee performance.